Microbial Load on Paper/Polymer Currency and Coins - Prasai, Tista; Yami, Kayo Devi; Joshi, Dev Raj (Nepal Journal of Science and Technology, 2010)
Currency notes and coins serve as an agency of transmission of microorganisms since they are passed freely from hand to hand as a medium of exchange. A research, with an objective to explore the microbial load on Nepalese paper/ polymer currency notes and coins, was carried out at the Environment Laboratory of Nepal Academy of Science and Technology, Khumaltar from November 2006 to May 2007. All together 63 samples of paper/polymer notes and coins from different professionals of different places at Kathmandu were collected and analyzed for the presence of microorganisms. Among the total tested paper/ polymer and coin samples, 98.4% were found to have heterotrophic aerobic bacteria, 87.3% were contaminated with coliform bacteria and 79.4% showed presence of Staphylococci. Contamination level was found in increasing order of coins> polymer notes>paper notes. The presence of high microbial load on currency notes and coins indicate the potentials of such currencies for possible disease spread in the human communities. Key words: currency notes; coins; heterotrophic bacteria; Coliform bacteria; Staphylococci DOI: 10.3126/njst.v9i0.3173 Nepal Journal of Science and Technology 9 (2008) 105-109